Struktur Pendidikan di Indonesia Dalam Perspektif Sejarah: Dari Masa Prasejarah Hingga Penjajahan Jepang - Arravi Firmansyah; Fauzan Ramadhan (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
This article focuses on examining the development of educational structures in Indonesia from prehistoric times to Japanese colonialism. Conceptually the structure of education regulates the education system which has an important role in describing the patterns and objectives of the implementation of the learning process. The structure of education continues to change with the times in order to adapt to developments that occur in a historical period. Therefore, this article aims to find out the structure of education in Indonesia from each period which consists of the prehistoric period to the Japanese occupation. The method used to compile this article is the historical method. This method is carried out in four stages, namely heuristics (gathering sources), criticism (testing sources), interpretation, and historiography (writing history. From this research it is known that the structure of Indonesian education from each period can be seen from prehistoric times to Japan complementing one another. each other with their own characteristics according to the conditions at that time.In addition, this study also provides an analysis that the ancestors of the Indonesian nation have long known the meaning of education, and have had an influence on the educational process in Indonesia to the present day